LIBERAL ISLAM AND ITS INFLUENCES ON THE DEVELOPMENT OF QURANIC EXEGESIS IN INDONESIA AND MALAYSIA - Amin, Ahmad Syaifuddin; Syarifah, Maisyatusy Syarifah (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2021)
Liberal Islamic movements in Indonesia and Malaysia are still active in voicing their thoughts although they have been strongly rejected by some local religious authorities. Even though it is no longer as massive as it used to be, its influence in the development of interpretations of the Qur’an is still very pronounced today. This study examines the influence of Liberal Islamic thought on the development of Quranic exegesis in Indonesia and Malaysia and focuses on Jaringan Islam Liberal (JIL) and Sisters in Islam (SIS), which are the most influential Liberal Islamic movements in Southeast Asia, especially in Indonesia and Malaysia. The data were collected from literature references with textual analysis as the main method. The results of this study indicate that the influence of JIL in the development of Quranic exegesis in Indonesia: first, the influence on the authority of interpretation by urging the Al-Quran. Second, the influence on the methodology of interpretation. Although JIL was not the initiator, JIL has a significant influence in bringing the flow of contextual methodology, maqāṣid approaches, hermeneutics, and other contemporary methods to Indonesia. Third, the influence on the popularization of new interpretive issues, such as human rights and gender. Meanwhile, SIS does not have a significant influence on the interpretation of the Quran in Malaysia like JIL, because: first, the hermeneutic approach used by SIS in the interpretation of the Quran is Amina Wadud’s hermeneutics, so she is more famous than SIS itself. Second, the liberal Islamic movement in Malaysia is strongly opposed by the Malaysian kingdom. Keywords: JIL, SIS, Quranic exegesis, Contextual, Hermeneutic